2004
DOI: 10.2139/ssrn.739024
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rates and Monetary Policy in Emerging Market Economies

Abstract: We compare alternative monetary policies for an emerging market economy that experiences external shocks to interest rates and the terms of trade. Financial frictions magnify volatility but do not affect the ranking of alternative policy rules. In contrast, the degree of exchange rate passthrough is critical for the assessment of monetary rules. With high pass-through, stabilising the exchange rate involves a trade-off between real stability and inflation stability and the best monetary policy rule is to stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
177
1
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(187 citation statements)
references
References 39 publications
4
177
1
5
Order By: Relevance
“… CPI inflation targeting is a realistic description of the conduct of Korean monetary policy following the abandonment of the fixed exchange rate (see Bank of Korea 2003 for details). Moreover, as shown by Devereux, Lane, and Xu (2004), CPI inflation targeting is the best monetary policy rule in an environment of low exchange rate pass‐through. …”
mentioning
confidence: 99%
“… CPI inflation targeting is a realistic description of the conduct of Korean monetary policy following the abandonment of the fixed exchange rate (see Bank of Korea 2003 for details). Moreover, as shown by Devereux, Lane, and Xu (2004), CPI inflation targeting is the best monetary policy rule in an environment of low exchange rate pass‐through. …”
mentioning
confidence: 99%
“…The investment adjustment cost parameter ψ I is set to 12.44 so that the elasticity of Tobin's Q with respect to the investment-capital ratio is 0.3, and the portfolio adjustment cost parameter ψ D is set to 0.0007 (Devereux et al 2006). The investment adjustment cost parameter ψ I is set to 12.44 so that the elasticity of Tobin's Q with respect to the investment-capital ratio is 0.3, and the portfolio adjustment cost parameter ψ D is set to 0.0007 (Devereux et al 2006).…”
Section: àmentioning
confidence: 99%
“…This is because in the face of sticky prices of nontraded and imported goods, the monetary authority must stabilize real exchange rates to stabilize the CPI inflation, which requires an increase in domestic interest rates to prevent an immediate large depreciation of real exchange rates (Devereux et al 2006;Smets and Wouters 2002). This is because in the face of sticky prices of nontraded and imported goods, the monetary authority must stabilize real exchange rates to stabilize the CPI inflation, which requires an increase in domestic interest rates to prevent an immediate large depreciation of real exchange rates (Devereux et al 2006;Smets and Wouters 2002).…”
Section: Effect Of External Shocks Under Alternative Fiscal-monetary mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study on the same subject reports very similar pass-through coefficients in Turkey: 50 percent for the WPI inflation and 40 percent for the CPI inflation (Leigh and Rossi, 2002). Devereux and Lane (2003) showed that if the exchange rate pass-through is low, both output volatility and inflation volatility in a floating exchange rate regime may be lower than under a fixed exchange rate regime. They conclude that a low rate of exchange rate pass-through may be an important prerequisite for the success of inflation targeting in emerging markets.…”
Section: Also Showed That Impulse-response Functions From the Var Estmentioning
confidence: 99%